1997
DOI: 10.1002/(sici)1096-9861(19970811)384:4<556::aid-cne5>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Central innervation of the rat ependyma and subcommissural organ with special reference to ascending serotoninergic projections from the raphe nuclei

Abstract: The subcommissural organ (SCO) and the cerebral ependyma receive serotoninergic innervation, but little is known about their origin in the raphe nuclei. Application of the retrograde tracer cholera toxin subunit B (ChB) in the third ventricle resulted in uptake in ependymal axons and backfilling of perikarya in the dorsomedian part of the dorsal raphe nucleus, immediately under the caudal aqueduct. By using dual staining with antisera against serotonin and ChB, a portion of the retrogradely labeled neurons was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
29
1
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 45 publications
8
29
1
3
Order By: Relevance
“…It may be inferred from morphological studies that 5HT is an important regulator for SCO functions, since this neurotransmitter is present in a dense nerve fiber plexus innervating the SCO of many mammalian species including bovine and rat (Møllgård and Wiklund 1979;Léger et al 1983;Bouchaud 1993;Mikkelsen et al 1997). Furthermore, in experimental studies with neurotoxins against 5HT in the rat, it has been shown that 5HT suppresses the secretory activity of the SCO (Léger et al 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be inferred from morphological studies that 5HT is an important regulator for SCO functions, since this neurotransmitter is present in a dense nerve fiber plexus innervating the SCO of many mammalian species including bovine and rat (Møllgård and Wiklund 1979;Léger et al 1983;Bouchaud 1993;Mikkelsen et al 1997). Furthermore, in experimental studies with neurotoxins against 5HT in the rat, it has been shown that 5HT suppresses the secretory activity of the SCO (Léger et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have studied the effects on CREB phosphorylation elicited by serotonin (5HT) and substance P (SP), which have previously been shown to be present in nerve fibers innervating the SCO (Ljungdahl et al 1978;Møllgård and Wiklund 1979;Léger et al 1983;Bouchaud 1993;Knigge and Schock 1993;Mikkelsen et al 1997;Schöniger et al 2001) or by ATP, an important neurotransmitter in the CNS and peripheral nervous system, shown to activate neurons and glial cells (for a review, see Zimmermann 1994) including SCO cells (Schöniger et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The DRC contains small round serotonergic neurons at its rostral extent and medium-size serotonergic neurons (Steinbusch 1984). Midline serotonergic neurons in the DRC have short thick dendrites orientated dorsoventrally, while the lateral serotonergic neurons in the DRC have longer dendritic processes extending dorsolaterally along the ventral surface of the cerebral aqueduct (Mikkelsen et al 1997;Simpson et al 1998).…”
Section: Anatomymentioning
confidence: 99%
“…The DRC also receives afferents from hypothalamic regions including the preoptic area, arcuate nucleus, and perifornical and lateral hypothalamic areas, and midbrain and brainstem regions including the IPN, laterodorsal tegmental area, and area postrema (Lee et al 2003). The DRC is the major source of serotonergic projections to the subfornical organ (Lind 1986) and subcommissural organ (Mikkelsen et al 1997), both circumventricular organs with a reduced blood-brain barrier, as well as the ependymal lining and the cerebral ventricles including the lateral, third, and fourth ventricles (Mikkelsen et al 1997;Simpson et al 1998). In addition, the DRC sends projections to the ventral hippocampus, amygdala, locus coeruleus (Imai et al 1986b), and midline thalamic nuclei, including the paratenial, paraventricular, and lateral parafascicular thalamic nuclei (Krout et al 2002).…”
Section: Afferent and Efferent Connectionsmentioning
confidence: 99%
“…The following connexions for the posterior commissure are reported: a) the coarse fibres directly connect with the nucleus of the posterior commissure and also indirectly through the nucleus of the posterior commissure or interstitial nucleus with the ipsilateral medial longitudinal bundle, b) Other fibres, chiefly coarse ones, connect with the regions of the tegmentum and the capsule of the red nucleus, c) fine fibres situated in the dorsal part of the commissure connect with the thalamus, d) the commissure consisting of horizontal fibres which may be traced in a lateral direction, it is thought that this connexion may be striatal,or possibly cortical, e) a small connexion with the habenular ganglia, and the habenulo-peduncular tracts, h) a fine connection with the pineal gland is also established (Keene, 1938). Also, studies in rat have demonstrated that the activity of the subcommissural organ depends on serotoninergic fibers originated in the raphe nuclei, some of which reach the subcommissural organ through the posterior commissure (Mikkelsen et al, 1997). In the chick brain, the tract of the posterior commissure emerges in the caudal pretectum as the first transversal tract.…”
Section: Anatomy Of the Posterior Commissurementioning
confidence: 99%